Effectiveness of the Village Fund Program in Aengdake Village, Bluto District, Sumenep Regency - Rofiqotul Ummah; Slamet Muchsin; Afifuddin (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
Aengdake Village is located at the eastern tip of Madura Island, where one of the Village Fund programs that has been successfully implemented to date is the health post, starting from toddlers to teenagers to the elderly. This health post is very useful, especially for the health of toddlers, to prevent stunting in children. At the same time, for teenagers, you can consult regarding the problems they are experiencing, and for the elderly, it is very useful. Many elderly people need treatment, especially their knees. This research aims to determine the implementation, improvement of quality, potential, and effectiveness of Village Funds in implementing funding programs in Aengdake Village, Bluto District, Sumenep Regency. This research uses a qualitative approach with descriptive research methods. The data collection techniques used in this research are interviews, observation, and documentation. The results of this research show that the implementation of the village fund program in Aengdake Village, Bluto District, Sumenep Regency includes (a) Government operations, village government facilities and infrastructure, population administration, civil registration and statistics, government administration, and land. (b) Development: education, health, public works and spatial planning, transportation, communication, and information. (c) Development: youth and sports, as well as PKK development. (d) Community empowerment: agriculture and animal husbandry, and increasing the capacity of village officials. (e) Unexpected costs.